The Tomato Guanylate-Binding Protein SlGBP1 Enables Fruit Tissue Differentiation by Maintaining Endopolyploid Cells in a Non-Proliferative State. Issue 10 (4th August 2020) - Musseau, Constance; Jorly, Joana; Gadin, Stéphanie; Sørensen, Iben; Deborde, Catherine; Bernillon, Stéphane; Mauxion, Jean-Philippe; Atienza, Isabelle; Moing, Annick; Lemaire-Chamley, Martine; Rose, Jocelyn K.C.; Chevalier, Christian; et al.
Abstract : The induction of polyploid divisions in the tomato gbp1 mutant reveals the role of the guanylate-binding protein in maintaining fruit tissue differentiation. Abstract: Cell fate maintenance is an integral part of plant cell differentiation and the production of functional cells, tissues, and organs. Fleshy fruit development is characterized by the accumulation of water and solutes in the enlarging cells of parenchymatous tissues. In tomato ( Solanum lycopersicum ), this process is associated with endoreduplication in mesocarp cells. The mechanisms that preserve this developmental program, once initiated, remain unknown. We show here that analysis of a previously identified tomato ethyl methanesulfonate-induced mutant that exhibits abnormal mesocarp cell differentiation could help elucidate determinants of fruit cell fate maintenance. We identified and validated the causal locus through mapping-by-sequencing and gene editing, respectively, and performed metabolic, cellular, and transcriptomic analyses of the mutant phenotype. The data indicate that disruption of the SlGBP1 gene, encoding GUANYLATE BINDING PROTEIN1, induces early termination of endoreduplication followed by late divisions of polyploid mesocarp cells, which consequently acquire the characteristics of young proliferative cells. This study reveals a crucial role of plant GBPs in the control of cell cycle genes, and thus, in cell fate maintenance. We propose that SlGBP1 acts as an inhibitor of cell division, a function conserved with the human hGBP-1 protein.